Electrochemical Preparation of Poly(N‐anthraquinoyl pyrrole) as High‐Performance Cathode Materials for Organic Lithium‐Ion Batteries. Issue 5 (8th March 2022) - Ye, Chaoxu; Zhang, Xin; Wang, Ying; Qin, Meng; Shi, Yanjun; Chen, Zhidong; Wang, Wenchang; Cao, Jianyu; Xu, Juan
Abstract : Anthraquinone and its derivatives show compelling electrochemical activities in lithium‐ion batteries due to their abundant redox‐active carbonyl groups and desirable π ‐conjugated structures. However, anthraquinone‐based compounds often suffer from inferior material utilization, a low‐capacity retention rate, and short cycle life due to poor conductivities and unexpected dissolution properties in supporting electrolytes during the charge/discharge cycles. To solve these problems, a novel grafted polymer, poly(N‐anthraquinoyl pyrrole) (e‐PAQPy), containing redox‐active anthraquinone subunits and conductive polypyrrole groups, is prepared by an electrochemical polymerization method and employed as the cathode material for organic lithium‐ion batteries. Polypyrrole backbone chain in e‐PAQPy is utilized both to bring into high electronic conductivity and to decrease the solubility of the anthraquinone subunits. As expected, the e‐PAQPy exhibits a high specific capacity (196.2 mAh g −1 at 0.1 C), good rate performance (70.8 mAh g −1 at 3 C), and long cycle stability (79% of the initial capacity after 500 cycles). Abstract : Novel poly(N‐anthraquinoyl pyrrole), containing redox‐active anthraquinone units and highly conductive polypyrrole groups, is prepared by an electrochemical polymerization method and employed as the cathode for a lithium‐ion battery, which exhibits a high specific capacitance (196.2 mAh g −1 at 0.1 C), good rate performance (70.8 mAh g −1 at 3 C), and long cycle stability (79% of the initial capacity retention rate after 500 cycles).